2021
DOI: 10.1136/neurintsurg-2021-017765
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of futile recanalization in patients undergoing endovascular treatment in the DIRECT-MT trial

Abstract: BackgroundFutile recanalization—when patients have a successful recanalization but fail to achieve a satisfactory functional outcome— is a common phenomenon of endovascular treatment of acute ischemic stroke (AIS). The present study aimed to identify the predictors of futile recanalization in AIS patients who received endovascular treatment.MethodsThis is a post-hoc analysis of the DIRECT-MT trial. Demographics, clinical characteristics, acute stroke workflow interval times, biochemical parameters, and imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 23 publications
6
45
1
Order By: Relevance
“…The mean age of the 99 patients who met the inclusion criteria was 72 years (IQR, 66-80) and 50.5% of these patients were women. The median baseline NIHSS score was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and the median baseline ASPECTS score was seven (IQR, 5-8). The numbers of patients who had occlusions in the ICA (isolated, T-or L-shaped, and tandem occlusions), M1, and M2 were 35 (35.4), 53 (53.5), and 11 (11.1%), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the 99 patients who met the inclusion criteria was 72 years (IQR, 66-80) and 50.5% of these patients were women. The median baseline NIHSS score was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and the median baseline ASPECTS score was seven (IQR, 5-8). The numbers of patients who had occlusions in the ICA (isolated, T-or L-shaped, and tandem occlusions), M1, and M2 were 35 (35.4), 53 (53.5), and 11 (11.1%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have identified predictors of FR after endovascular treatment in early time windows in patients with AIS (5)(6)(7)(8)(9)(10)(11)(12). However, few studies have investigated the predictors of FR in patients treated with MT in late time windows.…”
Section: Introductionmentioning
confidence: 99%
“…Several generic markers including age, gender, stroke severity, time from onset to puncture, and comorbidities (hypertension, diabetes, and atrial fibrillation) have been reported associated with clinical outcomes after EVT ( 4 , 7 , 22 ). In the present study, we also identified that the unfavorable functional outcome group was older, and had higher proportion of female, higher incidence of diabetes mellitus, and higher baseline NIHSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…The final cohort included 2261 patients: median (IQR) age 75 years (64-83), 46% female, median NIHSS 9 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). 34% received IVT alone, 41% MT alone and 25% both acute recanalization treatments (bridging approach).…”
Section: Baseline Characteristicsmentioning
confidence: 99%